Protein Content and Physical Characteristics of Chocolate Coated Manyung Fishtick (Arius thalassinus) - Abrian, Satriya; Widianto, David Indra; Iskandar, Amri; Pangestika, Widya; Maulid, Deden Yusman; Nusaibah, Nusaibah; Arumsari, Kusuma (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
Catfish (Arius thalassinus) is one of favourite consumed fish in pangandaran. It is widely used as a raw material for jambal roti salted fish. Apart from being used as salted fish, Catfish can also be processed into Fishstick which are rich in protein. The purpose of this reaserach is to determine the protein content and physical characteristic of Chocolate Coated Manyung Fishtick. Catfish meat used in the manufacture of fishstick is 0 %, 20%, 30%, 40%. The Protein contents were analysed using Kjeldahl methode. The result showed that fishtick with 40% Catfish meat has the highest protein content of 3,89%. The addition of Catfish meat had a significant effect on the characteristics of organoleptic properties. Based on hedonic testing, fishtick with the concentration of 40% fish meat is a formulation with the best acceptance to an aroma value of 7,63, a taste of 7,43 and a color of 7,17 wich indicates the spesification of the average value. The result of self life test also showed that the fishtick with concentration of 30% fish meat is the most durable according to aroma, taste, and texture analysis.